2023
DOI: 10.1101/2023.01.29.23285151
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Frequency and machine learning predictors of depressive, anxiety, obsessive-compulsive symptoms, and suicidal ideation among university students

Abstract: Introduction Prospective studies on mental health of students showed that young adults enroled in university are affected by poorer mental health than other working peers or adults, and this condition is responsible for a large proportion of disability-adjusted life-years Methods We enrolled 1388 students at the baseline (and 557 completed follow-up after six months) who reported their demographic information and completed self-report questionnaires on depressive, anxiety and obsessive-compulsive symptoms. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…Furthermore, the distribution of severity of depressive and anxiety symptoms revealed a strati cation of depressive and anxiety symptoms among university students. Our ndings were consistent with those of Piscoya-Tenorio et al and Meda et al in that a decreasing trend in the prevalence of depressive and anxiety symptom severity from mild to severe was observed [58,59]. In contrast, an increasing trend was reported in the study of Rabby et al [60].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, the distribution of severity of depressive and anxiety symptoms revealed a strati cation of depressive and anxiety symptoms among university students. Our ndings were consistent with those of Piscoya-Tenorio et al and Meda et al in that a decreasing trend in the prevalence of depressive and anxiety symptom severity from mild to severe was observed [58,59]. In contrast, an increasing trend was reported in the study of Rabby et al [60].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have reported that variations in factors such as hormone levels, socio-cultural factors, and stress coping styles among females were signi cantly associated with symptoms of depression and anxiety [59,[61][62][63][64]. Strained or con icted relationships between parents may weaken an individual's social and emotional support system, thus increasing vulnerability to stress and serving as a risk factor for depression and anxiety [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in our study, female participants are classified as having moderate anxiety and mild anxiety for male participants. Considering both genders, the medians of the BAI scores of this study are higher compared to the medians of both stages in [14]. Also, regarding the distribution of BAI scores, this study's IQR values of both genders are similar to those of female participants of the first stage.…”
Section: B Comparison With the Literaturementioning
confidence: 42%
“…In [14], Italian university students' mental health was investigated, considering students from different areas (e.g., Arts, Law, Economics, Medicine, Psychology and Mental Health, Neuroscience, and Pharmacy). The study considered two stages, the first one with 1,388 participants, and six months later, 557 persons participated in the second stage.…”
Section: A Literature Reviewmentioning
confidence: 99%